Uncontrolled Innate and Impaired Adaptive Immune Responses in Patients with COVID-19 Acute Respiratory Distress Syndrome - Hue, Sophie; Beldi-Ferchiou, Asma; Bendib, Inés; Surenaud, Mathieu; Fourati, Slim; Frapard, Thomas; Rivoal, Simon; Razazi, Keyvan; Carteaux, Guillaume; Delfau-Larue, Marie-Héléne; Mekontso-Dessap, Armand; Audureau, Etienne; et al. (American journal of respiratory and critical care medicine, 2020)
Uncontrolled inflammatory innate response and impaired adaptive immune response are associated with clinical severity in patients with coronavirus disease (COVID-19). To compare the immunopathology of COVID-19 acute respiratory distress syndrome (ARDS) with that of non-COVID-19 ARDS, and to identify biomarkers associated with mortality in patients with COVID-19 ARDS. Prospective observational monocenter study. Immunocompetent patients diagnosed with RT-PCR-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and ARDS admitted between March 8 and March 30, 2020, were included and compared with patients with non-COVID-19 ARDS. The primary clinical endpoint of the study was mortality at Day 28. Flow cytometry analyses and serum cytokine measurements were performed at Days 1-2 and 4-6 of ICU admission. As compared with patients with non-COVID-19 ARDS ( = 36), those with COVID-19 ( = 38) were not significantly different regarding age, sex, and Sequential Organ Failure Assessment and Simplified Acute Physiology Score II scores but exhibited a higher Day-28 mortality (34% vs. 11%, = 0.030). Patients with COVID-19 showed profound and sustained T CD4 ( = 0.002), CD8 ( < 0.0001), and B ( < 0.0001) lymphopenia, higher HLA-DR expression on monocytes ( < 0.001) and higher serum concentrations of EGF (epithelial growth factor), GM-CSF, IL-10, CCL2/MCP-1, CCL3/MIP-1a, CXCL10/IP-10, CCL5/RANTES, and CCL20/MIP-3a. After adjusting on age and Sequential Organ Failure Assessment, serum CXCL10/IP-10 ( = 0.047) and GM-CSF ( = 0.050) were higher and nasopharyngeal RT-PCR cycle threshold values lower ( = 0.010) in patients with COVID-19 who were dead at Day 28. Profound global lymphopenia and a "chemokine signature" were observed in COVID-19 ARDS. Increased serum concentrations of CXCL10/IP-10 and GM-CSF, together with higher nasopharyngeal SARS-CoV-2 viral load, were associated with Day-28 mortality.